School Interruption and Family Arrangements: Contributions to the Drop-out Literature from the Analysis of Family-School Links (Revista Peruana de Investigación Educativa, 2010)
Studies on social exclusion and inequality within education have shown, from different points of analysis, how working class groups are in fact excluded in diverse ways, with most of the explanations associated with family economic conditions. However, studies in the last decade, from the sociology of education, show that within groups in similar economic conditions, different educational outcomes are possible. In this context, the question that occupies the present study is the following: Why some young men and women living in apparently similar contexts manage to remain in the school system while others leave it?
Keywords: school student relationship; rural education; educational anthropology; rural youth